EKOLOGIK VA ANTROPOGEN OMILLAR HAMDA ULARNING O‘SIMLIKLARNI O‘SISH VA RIVOJLANISHIGA TA’SIRI - Po‘latov , Sarvar Mustafoyevich; Xashimova , Madina Raxmonberdi qizi (Educational Research in Universal Sciences, 2023)
Abiotic factors include moisture, temperature, light, air, pressure, flow, day length, mechanical structure of soil, air and water permeability, mineral composition of soil and water, salinity, and others. Biotic factors include the effect of plants on other organisms, the effect of animals on other organisms, anthropogenic factors caused by human activities and changes in the natural environment, and anthropogenic factors include human economic activity.